UPAH MINIMUM YANG DICITA-CITAKAN - Pangaribuan, Piatur (Jurnal de Facto, 2014)
Stipulation of minimum wage by the Governor either district provincial, cities or at cities level often give rise to the issue between the worker union/labor union with employers and often occur demonstration call for a high minimum wage increasing and on the other side a lot of entrepreneurs who are not able to meet the minimum wage has been set and ultimately conduct termination of employment. According to the researcher, the Governor in setting the minimum wage did not refer to legal aspects of the determination of the minimum wage. Government should refer to appropriate regulation that it has already regulated under specific law namely, Peraturan Menteri Tenaga Kerja No.: PER-01/MEN/1999 and the latest amendment KEP-226/MEN/2000 tentang Upah Minimum, so that it able to accommodate all interests of unions, employers and the unemployed labor force as well.